2023
DOI: 10.1021/acsanm.3c05787
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Cinnamaldehyde, Furanic, and Aromatic Aldehydes over a Z-Scheme Heterojunction Photocatalyst Constituted of Pd NPs Supported on g-C3N4/ZnO Nanocomposite

Rajat Ghalta,
Arzoo Chauhan,
Rajendra Srivastava

Abstract: In this study, a Z-scheme heterojunction photocatalyst is fabricated by systematically manipulating and integrating g-C 3 N 4 and ZnO. The Z-scheme g-C 3 N 4(x) /ZnO (y) exhibits enhanced charge separation and migration, confirmed through photoluminescence (PL), time-correlated single-photon counting spectroscopy, and electrochemical impedance spectroscopy. Pd NPs, with an elevated work function and low Fermi energy level, are decorated onto the heterojunction, further amplifying charge separation, as revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…S17a†). 69 It induced upward band bending in CN and downward band bending in band edges of BMO near the interface (refer to Fig. 10a(i) and (ii)).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…S17a†). 69 It induced upward band bending in CN and downward band bending in band edges of BMO near the interface (refer to Fig. 10a(i) and (ii)).…”
Section: Resultsmentioning
confidence: 92%
“…70–72 Upon incorporating Pd NPs into the heterojunction, the Fermi level of the CN/rGO/BMO(2 : 1) composite aligned with the Fermi level of Pd NPs at 5.12 eV vs. V ac . 69 It led to resifting of the Fermi level at 4.78 eV vs. V ac for 0.5%Pd@CN/rGO/BMO(2 : 1) and 4.93 eV vs. V ac for 5%CN/rGO/BMO(2 : 1) catalysts (Fig. S18b and c†).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Direct hydrogenation using molecular H 2 occurred in IPA as a solvent under irradiation with a 150 W white LED light. 84 The study showed selectivity modulation between BHMF and BHMTHF (a ring-reduced product) by adjusting the reaction time and Pd loading. Over 1% Pd@C 3 N 4(0.73) /ZnO (0.27) and 3% Pd@C 3 N 4(0.73) /ZnO (0.27) catalysts, 82% and 92% product selectivity were achieved for BHMF and BHMTHF, respectively, in 6 h and 8 h (Table 1, entries 20 and 21).…”
Section: Current Studies Covering the Photocatalytic Reduction Of The...mentioning
confidence: 94%